The Effect of Conventional Strategy Toward Reading Comprehension of Narrative Text at Eleventh Grade Social Science of SMA Negeri 1 Talamau Pasaman Barat - Yessy Marzona (Fakultas Sastra Universitas Ekasakti, 2020)
In teaching reading comprehension, teaching strategy influence students’ reading comprehension. Strategy which was used in this experimental research was conventional strategy. Conventional strategy can be used as teaching strategy in teaching reading comprehension. The purpose of this research was to find out whether the students who are taught by conventional strategy have better reading comprehension of narrative text than those who are not taught by conventional strategy. This research was an experimental research with factorial design 2x2. It was conducted at SMA Negeri 1 Talamau Pasaman Barat. The population of this research was eleventh grade social science students with total population of 40 students. The sample was taken by using total sampling; so all of population was taken as sample. XI IPS 2 was experimental class and XI IPS 1 as control class. The instruments of this research were reading comprehension test and questionnaire. The data was analyzed by two ways ANOVA (ANOVA 2x2). The results of this research are (1) Reading comprehension of students who are taught by conventional strategy is not better than reading comprehension of students who are not taught by conventional strategy. Fo = 196.582 > Ft = 2.69, it means that Ha is rejected.